Pengaruh Kualitas Produk Terhadap Kepuasan Konsumen Toko Amira Meubel Kota Gorontalo - Fandriananto Sayedi; Rosman Ilato; Radia Hafid; Usman Moonti; Sudirman Sudirman (State University of Gorontalo, 2023)
The present research aimed to determine the effect of product quality on customer satisfaction at Amira Furniture Store, Gorontalo City.This research employed a quantitative approach with a survey research method. The data used were primary data obtained from disributing questionnaires to customers of Amira Furniture Store, Gorontalo City, with a sample of 40 respondents. In the meantime, the data analysis technique used simple linear regression.In conclusion, product quality had a significant effect on customer satisfaction at the Amira Furniture Store, Gorontalo City. In addition, product quality effectively and efficiently had a significant effect on customer satisfaction for 51.4%, while the remaining 48.6% were affected by other variables examined in this research. This result signified that product quality significantly affected customer satisfaction at Amira Furniture Store, Gorontalo City.